Bergabungnya International Organization for Migration (IOM) Menjadi Agen Migrasi Perserikatan Bangsa Bangsa (PBB) - Juliani Az Zahra; Apriwan; Setyaka, Virtuous (Hubungan Internasional Universitas Andalas, 2025)
After World War II, Europe was plagued by problems due to population density and the high flow of migrant mobility entering Europe. This phenomenon encouraged countries to form an organization to manage the movement of people and logistics in the European region known as the International Organization for Migration (IOM). Despite being established with a limited, temporary mandate, and outside the UN framework, IOM managed to grow, proving its expertise and role in various global migration events to become one of the leading actors in global migration. However, in 2016, IOM decided to form a more formal bond of cooperation by signing the 2016 Agreement which also marked the incorporation of IOM into the UN, making IOM a